Synchronization of sprinting between blind and guide sprinters: a case study - Nagahara, R. (ISBS Proceedings Archive (Michigan), 2020)
This study aimed to evaluate the magnitude of synchronization between blind and guide sprinters for elite and sub-elite pairs. Two pairs of male blind sprinters and their guide sprinters performed 60-m sprints during which ground reaction force and sprinting motion were recorded. Although flight time and propulsive force in sub-elite pair showed significant and moderate difference between the sprinters, there were trivial and small differences in variables between the sprinters of elite pair. Moreover, the correlation (r = 0.97 and 0.84) in the thigh angle in the sagittal plane between blind and guide sprinters was high with no phase shifting for the elite pair compared to the sub-elite pair during the initial acceleration phase. The results indicate that the magnitude of synchronization is likely high in an elite pair of blind and guide sprinter especially during the initial acceleration phase.